The region of the IncN plasmid R46 coding for resistance to beta-lactam antibiotics, streptomycin/spectinomycin and sulphonamides is closely related to antibiotic resistance segments found in IncW plasmids and in Tn21-like transposons. - Hall, R M (1987)
The nucleotide sequence of a 2.5 kb segment of the pKM101 (R46) genome has been determined. The 1.3 kb from a BamHI site at 153 to base 1440 differs by only 2 bases from a part of the published sequence of the aadB (gentamicin resistance) gene region including the coding region for the N-terminal 70 amino acids of the predicted aadB product. The same sequence has been found 5'-to the dhfrII gene of R388 and to the aadA gene of Tn21 (R538-1). Three open reading frames are located in this region, two on the same strand as the resistance genes and one on the complementary strand. The latter predicts a polypeptide of 337 amino acids, whose N-terminal segment is 40% homologous to the predicted product of an open reading frame of 179 amino acids located next to the dhfrI gene of Tn7. The oxa2 (oxacillin resistance) gene predicts a long polypeptide commencing with (the N-terminal) 70 amino acids of the aadB product. A similar arrangement is found in the aadA gene of R538-1. The N-terminal segment of an aadA gene is located 3'- to oxa2, separated by 36 bases. Sequences surrounding the BamHI site are identical to sequences 5'- to the tnpM gene of Tn21 and homology ceases where homology between Tn21 and Tn501 commences. The possibility that this antibiotic resistance segment is a discrete mobile DNA element is discussed.